Attitudes of cow-calf producers toward NAIS are guarded - Breiner, S.J.; Grau, S.A.; Barnhardt, B.B.; Bryant, A.M.; Boone, Kris; Blasi, Dale A.; Schroeder, Ted C.; Breiner, Ryan M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The introduction of a National Animal Identification System (NAIS) into the United States has generated much confusion and controversy. The goal of the NAIS is to utilize 48-hour traceback in the event of an animal disease outbreak, identify all animals that have had contact with the diseased animal, and link animals to their premises of origin. The NAIS has led to new technology and guidelines with the potential to change the production and marketing landscape of the beef industry. Moreover, these advances have led to public policy issues that have changed the rhetoric of the industry. The objective of this study was to examine perceptions and attitudes of cowcalf producers toward emerging beef technologies and policy issues through a nationwide mail survey. By understanding the demographics of today’s producers in addition to their current practices, the industry can work toward better educating and understanding the concerns of these producers.
Keywords: Beef; Cattle; National Animal Identification System (NAIS); Cow-calf producers